EVALUATION OF CREDIT ACCESSIBILITY AND PERFORMANCE OF SMALL AND MEDIUM AGRICULTURAL ENTERPRISES IN BAUCHI LOCAL GOVERNMENT, BAUCHI STATE, NIGERIA - Sambo, I. M.; Danwanka, H. A.; Usman, H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examines credit accessibility and its impact on the performance of small and medium agricultural enterprises (SMEs) in Bauchi Local Government, Bauchi State, Nigeria. Data were collected through structured questionnaires from a sample of 201 respondents. Analysis was conducted using descriptive and inferential statistics. The findings reveal that 59.7% of respondents had adequate start-up capital, while 51.2% applied for credit in the past year. Furthermore, 57.7% reported that credit improved their businesses. Regarding credit services, 37.3% of respondents rated them as neutral, while 64.2% were members of cooperative societies. The study found no significant improvement in income levels after credit access (mean income before credit: ₦21,850.74; after credit: ₦21,706.47). However, expenditure increased from ₦20,435.32 to ₦24,032.34. Large-scale purchases increased slightly from 11.9% to 14.9%, while 51.2% of respondents reported improved daily income, and 58.2% observed increased savings. The results suggest that while credit access positively influences business expansion and savings, its impact on income growth remains limited. The study identifies barriers such as high interest rates, collateral requirements, and bureaucratic constraints as key challenges to credit accessibility. To enhance SME growth, the study recommends improving credit accessibility, implementing financial literacy programs, and reducing bureaucratic hurdles in the credit application process.